Extending the Theory of Planned Behavior: Predicting Chinese Muslims’ Halal Meat Purchase Intention - Nur Azizatul Musyarofah; Yuli Handayani; Sri Hartini (Inovasi Analisis Data, 2025)
Objective: This study has the purpose to analyse the factors that affect the of the Behavioural Intention (BI) of consumer on halal food consumption in Indonesia which either consists of; the Attitude, Subjective Norms, Perceived Behavioural Control, Trust, and the Availability.Methods: This study used a quantitative approach, with data obtained from a structured questionnaire for 700 respondents from major cities in Indonesia. Descriptive analysis, multiple regression analysis, and Structural Equation Modeling (SEM-PLS) are used for analyzing the data to test the relationships that have been proposed among the constructs.Results: The findings of this study show that Attitude, Subjective Norms, Perceived Behavioral Control, Trust, and Availability have a positive influence on Behavioral Intention. Also, trust was found to mediate the relationship of attitude with behavioral intention, while availability moderated between perceived behavioral control & behavioral intention.Novelty: By investigating the mediating effect of Trust and the moderating role of Availability in the relationship between all key drivers in predicting Behavior Intention to consume halal food, this study extends literature regarding consumer behavior in halal food market.Theory and Policy Implications: Theoretically, the paper adds to the existing body of knowledge on Theory of Planned Behavior by introducing Trust and Availability as significant determinants of consumer behavior. These insights are relevant to policymakers and marketers in the halal food industry, as they can help improve accessibility to safe and quality products, promote consumer trust, and develop strategies for the consumption of halal food.